Time to switch from CLSI to EUCAST? a Southeast Asian perspective - Cusack, T; Ashley, E; Ling, C; Roberts, T; Turner, P; Wangrangsimakul, T; Dance, D (Elsevier, 2019)
Despite the importance of antimicrobial susceptibility testing (AST) to clinical management of infection and to antimicrobial resistance (AMR) surveillance, methodologies and breakpoints of the two most commonly used systems worldwide, CLSI and EUCAST, are far from harmonized. Most laboratories in resource-constrained settings such as Southeast Asia, including our own, currently follow CLSI disk diffusion AST guidelines. Many aspects of the EUCAST system, not least the freely available nature of all output, are likely to be attractive to laboratories in our setting, but published reports of the practical differences between CLSI and EUCAST methodologies are lacking. Our manuscript highlights key differences between CLSI and EUCAST disk diffusion AST methodologies, and the practical implications of adopting EUCAST guidelines in our laboratory network. We discuss potential barriers to adoption of EUCAST guidelines in resource-Clinical Microbiology and Infection constrained settings including difficulties in obtaining horse blood for media supplementation and the need for an MIC method for AST of N. gonorrhoeae. We highlight the need for a globally harmonized AST system that is practical and freely available, and we hope this commentary will be useful for laboratories considering switching between CLSI and EUCAST.